Expanding the phenotype of SCA19/22: Parkinsonism, cognitive impairment and epilepsy. (December 2017) - Huin, Vincent; Strubi-Vuillaume, Isabelle; Dujardin, Kathy; Brion, Marine; Delliaux, Marie; Dellacherie, Delphine; Cuvellier, Jean-Christophe; Cuisset, Jean-Marie; Riquet, Audrey; Moreau, Caroline; Defebvre, Luc; Sablonnière, Bernard; et al.
Abstract: Introduction: Spinocerebellar ataxia types 19 and 22 (SCA19/22) are rare conditions in which relatively isolated cerebellar involvement is frequently associated with cognitive impairment. Here, we report on new clinical features and provide details of the cognitive profile in two SCA19/22 families. Methods: Two families displaying an autosomal-dominant form of cerebellar ataxia underwent clinical examinations and genetic testing. Results: In addition to the classical clinical features of SCA, a wide spectrum of cognitive disorders (including visuospatial impairments) was observed. Eight patients had mild Parkinsonism, and five had epilepsy. Genetic testing showed that the KCND3 mutation (c.679_681delTTC, p.F227del) was present in both families. Conclusions: Our findings broaden the phenotypic spectrum of SCA19/22, and suggest that KCND3 should be included in the list of candidate genes for epilepsy, Parkinsonism and cognitive impairment. Highlights: SCA19 and SCA22 (caused by KCND3 gene mutations) are rare forms of inherited ataxia. We observed Parkinsonism is a high proportion of individuals with SCA19/22. Epilepsy seems to be a feature of SCA19/22. We characterized cognitive and behavioral disorders. KCND3 may be a candidate gene for epilepsy, Parkinsonism and cognitive disorders.